Reference materials for the determination of contaminants in milk and milk products - J. Táborský; A. Hejtmánková; J. Dolejšková (Czech Journal of Food Sciences, 2003)
In this review, the latest information is given about the reference materials for the determination of contaminants in milk and milk products. Certified reference materials for the determination of contaminating chemical elements, organochlorine pesticides, polychlorinated biphenyls, dibenzodioxins, dibenzofurans, and aflatoxin M1 are presently available. Properties of these reference materials and possibilities for their use are discussed together with the maximum tolerances of contaminants in milk and milk products. The basic information about the producers and distributors of the reference materials in this area is provided.